The Ability of Spirulina sp. Microalgae as A Phytoremediation Agents in Liquid Waste of Handling Fish from Cemara Market, Medan - Astrid Fauzia Dewinta; Eddie Satria Hartono; Eri Yusni; Ipanna Enggar Susetya; Rizky Febriansyah Siregar (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightMicroalgae Spirullina sp. can remediate BOD levels reach on 75.59% with the experiment was 30% liquid waste and 70% water.Microalgae Spirullina sp. can remediate COD levels reach on 79.19% with the experiment was 30% liquid waste and 70% water.Microalgae Spirullina sp. can remediate TSS levels reach on 83.54% with the experiment was 30% liquid waste and 70% water.Microalgae Spirullina sp. can remediate ammonia levels reach on 89.15% with the experiment was 30% liquid waste and 70% water.AbstractContamination material from fish market activities, namely fish handling liquid waste, is a problem facing the city of Medan today. Reduce the level of liquid waste pollutants can be done biologically by using microalgae organisms. One of them is like microalgae Spirulina sp. This study aims to determine the ability of Spirulina sp. for reducing the levels of pollutants in liquid waste of handling fish.There search method was use a Completely Randomized Design (CRD) with five treatments and three replications. Addition of 100 mL of inoculant Spirulina sp. with a density of 1x105 ind/mL of liquid waste mixed with fresh water with to reach a volume of 1000 mL. Each liquid waste concentration of 30%, 60%, 80%, 100%, and control (0%) added 1 mL Walne fertilizer. The results of initial measurements of liquid waste for parameters BOD, COD, TSS, ammonia, and phosphate, respectively are 26.50mg/L, 4400mg/L, 894mg/L, 1.10mg/L, and 16.7 mg/L. Based on the results, the best reduction in BOD level occured in the treatment of 30% (pA) of liquid waste is 17.64 mg/L with phytoremediation efficiency of 75.59%. The best reduction in COD levels occurred in the treatment of 30% (pA) of liquid waste is 1301.12 mg/L with phytoremediation efficiency of 79.19%. The best reduction in TSS levels occurred in the treatment of 60% (pB) of liquid waste is 411 mg/L with phytoremediation efficiency of 83.54%. The best reduction in ammonia levels was at 30% (pA) treatment, which was 0.38 mg/L with phytoremediation efficiency of 89.15%. While the best decrease in phosphate levels occurred in the control treatment (pK), which was 4.45 mg/L with phytoremediation efficiency of 97.35%.